Duodenal Bulb Mucosa with Hypertrophic Gastric Oxyntic Heterotopia in Patients with Zollinger Ellison Syndrome. (14th June 2009) - Kohan, Emil; Oh, David; Wang, Hank; Hazany, Salar; Ohning, Gordon; Pisegna, Joseph R.
Abstract : Objectives . Zollinger-Ellison Syndrome (ZES) results in hypersecretion of gastric acid (via gastrinoma) leading to peptic ulcers, diarrhea, and abdominal pain. We describe the novel discovery of hypertrophic, heterotopic gastric mucosa in the proximal duodenal bulb in patients with ZES, which we hypothesize results in an increased incidence of postbulbar ulcers in patients with ZES (a mechanism previously unreported). We determined the incidence of the novel finding of duodenal gastric oxyntic hypertrophic heterotopia (GOH) in patients with ZES. Methods . Seven patients with ZES were enrolled. The diagnosis of ZES was established by hypergastrinemia, gastric acid hypersecretion, and a positive secretin test or based on biopsy specimens (evaluated via tissue staining). Basal acid output (BAO) and baseline gastrin secretion were determined by established methods. Endoscopic examinations with methylene blue staining and biopsy of the gastric and duodenal mucosa were conducted in all patients every 3–6 months for an average of 5 years. Results . The duodenal mucosa demonstrated hypertrophic GOH in 5 out of 7 patients with ZES and an intact stomach and duodenum. Biopsies from the bowel mucosa demonstrated patchy replacement of surface epithelium by gastric-type epithelium with hypertrophic oxyntic glands in the lamina propria in 5 patients. Two of the patients had no evidence of GOH in the duodenal bulb. Patients with GOH had an average serum gastrin level of 1245 pg/mL and BAO of 2.92 mEq/hr versus 724 pg/mL and 0.8 mEq/hr in patients without GOH. Conclusions . This study demonstrated the presence of duodenal mucosa with GOH in 5 out of 7 patients with ZES and an intact stomach and duodenum. The presence of hypertrophic and heterotopic gastric mucosa is proposed to result from increased gastrin levels and may contribute to the increased incidence of postbulbar ulcers in these patients.